Analisis penggunaan anggaran biaya operasional dan pendapatan dalam menilai kinerja keuangan pada PT. Gerbang Nusa Perkasa di Manado - Junike Tesalonika Aror; David P. E. Saerang; Natalia Y. T. Gerungai (Yayasan Widyantara Nawasena Raharja, 2026)
This study examines the role of operational cost and revenue budgeting in assessing firm performance by integrating budget variance analysis with financial ratio evaluation. Prior studies predominantly rely on financial ratios without explicitly linking them to budget effectiveness, creating a research gap in performance assessment frameworks. Using a case study approach on PT. Gerbang Nusa Perkasa, this research employs a mixed analytical framework combining variance analysis and liquidity, solvency, and profitability ratios. The findings reveal that although the firm demonstrates strong profitability and liquidity, budget variance analysis uncovers inefficiencies in cost planning that are not captured by traditional ratio analysis. This study contributes by proposing a more comprehensive performance evaluation model that links budgeting effectiveness with financial outcomes.